Local Language as Social Capital: A Sociolinguistic Study in Building the Cohesion of a Multicultural Society - Gold Sunday Chukwuemeka; Muhammad Yamin; Nini Arianti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Local languages are one of the important instruments in building social cohesion in a multicultural society. In Indonesia, regional language diversity not only functions as a means of communication, but also as social capital that strengthens social ties, collective identity, and solidarity between citizens. This study aims to analyze the role of local languages in building the cohesion of multicultural communities through a sociolinguistic perspective. The research was conducted with a qualitative approach through literature studies, text analysis, and comparative studies of several practices of using local languages in social interactions. The results of the study show that local language is a symbol of identity that strengthens a sense of belonging in a certain community as well as a means of identity negotiation in a multicultural context. On the other hand, local languages play a role in building social networks based on common beliefs and norms that strengthen social solidarity. However, challenges arise when local languages experience a decline in function due to the dominance of national and global languages. Therefore, the preservation of local languages through education, media, and cultural activities needs to be strengthened to maintain its role as social capital. This study emphasizes that local languages are not only cultural heritage, but also a strategic instrument to strengthen social cohesion in the midst of the plurality of Indonesian society.